2015
DOI: 10.1177/0310057x1504300207
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Haemodilution with Albumin on Coagulation in Vitro as Assessed by Rotational Thromboelastometry

Abstract: We investigated the in vitro viscoelastic changes of progressive haemodilution with 4% albumin compared with normal saline (NS) using rotational thromboelastometry (ROTEM®, Pentapharm Co., Munich, Germany). Whole blood samples obtained from 20 healthy volunteers were diluted in vitro with 4% albumin or NS by 10%, 20% and 40%. Fibrinogen concentration and ROTEM® (EXTEM [screening test for the extrinsic haemostasis system], FIBTEM [EXTEM-based assay for the fibrin part of the clot]) variables including coagulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Dilution of sample with IS caused shortening of CT on INTEM and EXTEM as has been demonstrated previously; however, incubation with hexagonal phase PL resulted in further shortening of CT on INTEM and EXTEM confirming PL‐dependent nature of the prolongation (Figure ). Of interest, delta StaClot was positively correlated with delta CT INTEM (difference between CT INTEM spiked with IS and CT INTEM incubated with PL) r = .72, P = .012, as well as with delta CT EXTEM r = .74, P = .036.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Dilution of sample with IS caused shortening of CT on INTEM and EXTEM as has been demonstrated previously; however, incubation with hexagonal phase PL resulted in further shortening of CT on INTEM and EXTEM confirming PL‐dependent nature of the prolongation (Figure ). Of interest, delta StaClot was positively correlated with delta CT INTEM (difference between CT INTEM spiked with IS and CT INTEM incubated with PL) r = .72, P = .012, as well as with delta CT EXTEM r = .74, P = .036.…”
Section: Resultssupporting
confidence: 81%
“…Our study showed approximately 25% shortening with the addition of IS. Prior studies with ROTEM and TEG showed shortened CT EXTEM with 10% dilution of WB by IS and diminished reaction (R) time on kaolin‐induced TEG with 15%‐30% IS dilution . These hypercoagulable changes in whole blood at low levels of hemodilution are believed to be due to the different effects of diluting pro‐ versus anticoagulant factors in blood, particularly antithrombin (AT), as low‐level dilution did not change R time values in AT‐deficient plasma and hemodilution‐induced coagulation enhancement is attenuated, but not completely prevented, if AT levels are restored to prediluted range .…”
Section: Discussionmentioning
confidence: 97%
“…Although Jones et al 25 showed that D40 enhanced endogenous fibrinolysis in 20 patients undergoing endovascular stenting, we could not demonstrate fibrinolysis in this in vitro model. Previous studies demonstrated that fibrinogen concentration decreases proportionally with progressive in vitro haemodilution with intravenous fluids 23 . Using MEA, we did not demonstrate impaired platelet receptor function when dextran was added to WB.…”
Section: Discussionmentioning
confidence: 97%
“…The basic principle of the TEM can account for the disagreement . No significant variations were seen in pH, ionic Ca and blood cellular components after PE; in spite of that, TEM is performed in whole blood and several variables that are relevant during the PE, that is changes in blood viscosity due to albumin, magnesium, hemodilution and patient condition can affect the results. Because of this, TEM could offer information beyond the standard coagulation test, detecting patients at highest risk of bleeding after PE.…”
Section: Discussionmentioning
confidence: 99%